2007
DOI: 10.1111/j.1365-2559.2007.02824.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical biomarkers of value in distinguishing primary ovarian carcinoma from gastric carcinoma: a systematic review with statistical meta‐analysis

Abstract: Provided sufficient numbers of cases are studied, analysis of studies comparing antigen expression for diagnostic purposes in tumours from two body sites is likely to be supported in the wider literature. The design of such comparative studies is informed by aggregating data from single tumour studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 112 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…RT-PCR proves the existence of tumor cells by amplifying mRNA in tumor cells, and it is considered to be a specific method with high sensitivity to detect residual tumor cells or hidden metastasis (Jennings et al, 2012). CK-7 is expressed stably in primary ovarian cancer cells or metastases from ovary and is a common marker to determine whether the metastases came from ovary (Heatley, 2008). As a common cancer indicator for epithelial ovarian cancer, CA125 is highly expressed in ovarian cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR proves the existence of tumor cells by amplifying mRNA in tumor cells, and it is considered to be a specific method with high sensitivity to detect residual tumor cells or hidden metastasis (Jennings et al, 2012). CK-7 is expressed stably in primary ovarian cancer cells or metastases from ovary and is a common marker to determine whether the metastases came from ovary (Heatley, 2008). As a common cancer indicator for epithelial ovarian cancer, CA125 is highly expressed in ovarian cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In related genes which mediate invasion and metastasis of ovarian tissues, the expression of CK-7 is relatively stable in primary ovarian cancer or metastases from ovaries. CK-7 is a common indicator to judge whether the metastases are from ovaries (Heatley, 2008). CA125 is a common tumor marker for epithelial ovarian cancer and its expression is relatively high in ovarian tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Heatley (13) used in silico data mining with metaanalysis to compare MUC2 between OMTs and gastric cancer, with positive frequencies of 69% and 43% respectively. Hanski et al (14) reported expression of MUC2 OMTs, breast, colorectal, and pancreatic cancers.…”
Section: Wang and El-bahrawymentioning
confidence: 99%